A randomized, controlled trial of enhanced cleaning to reduce contamination of healthcare worker gowns and gloves with multidrug-resistant bacteria - Hess, Aaron S. (2013)
OBJECTIVE: To determine whether enhanced daily cleaning would reduce contamination of healthcare worker (HCW) gowns and gloves with methicillin-resistant Staphylococcus aureus (MRSA) or multidrug-resistant Acinetobacter baumannii (MDRAB). DESIGN: A cluster-randomized controlled trial. SETTING: Four intensive care units (ICUs) in an urban tertiary care hospital. PARTICIPANTS: ICU rooms occupied by patients colonized with MRSA or MDRAB. INTERVENTION: Extra enhanced daily cleaning of ICU room surfaces frequently touched by HCWs. RESULTS: A total of 4,444 cultures were collected from 132 rooms over 10 months. Using fluorescent dot markers at 2,199 surfaces, we found that 26% of surfaces in control rooms were cleaned and 100% of surfaces in experimental rooms were cleaned (p < 0.001). The mean proportion of contaminated HCW gowns and gloves following routine care provision and before leaving the rooms of patients with MDRAB was 16% among control rooms and 12% among experimental rooms (RR: 0.77, 95% CI: 0.28 – 2.11, p = 0.230). For MRSA, the mean proportions were 22% and 19%, respectively (RR: 0.89, 95%: 0.5 – 1.53, p = 0.158). DISCUSSION: Intense enhanced daily cleaning of ICU rooms occupied by patients colonized with MRSA or MDRAB was associated with a nonsignificant reduction in contamination of HCW gowns and gloves after routine patient care activities. Further research is needed to determine whether intense environmental cleaning will lead to significant reductions and fewer infections.